Impact of Green Logistics Activities on Circular Economy: Panel Data Evidence from ASEAN - Chonmapat Torasa; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
Green logistic considers those actions which can minimize the ecological impact of logistics activities. The purpose of this paper is to examine the impact of green logistics activities on the circular economy indicators of ASEAN. This study has considered four ASEAN members including Malaysia, Indonesia, Thailand, and Singapore, from 2000 to 2015 with yearly observations. For analyzing the relationship between selected factors of green logistics activities and circular economy, three panel models under the title of ordinary least square OLS, fixed effect and random effect was applied. The main findings of the study show that there is significant influence of Transportation and communication (TC) on recycling rate of selected economies under all three panel models. However, the factor of mining, manufacturing, and construction has shown their significant and positive impact on the recycling rate in ASEAN. Similarly, the effect of TC on specific waste streams is found to be significant and negative under all panel estimators. Further, the factor of MMC is significantly and positively influencing on contribution of recycled materials to raw material demands in selected regions. However, trade of recyclable raw materials has shown an adverse influence from TC under full sample of the study. The findings of the study would be of significant support to the policymakers and various stakeholders in ASEAN economies while exploring the relationship between green logistics activities and selected indicators of circular economy. To the best of author’s knowledge, there has been a dearth of research studies specifically with empirical findings, examining the association between green logistics and circular economy. Therefore, this research could be assumed as tentative addition to the literature of economics.  However, present study has some limitations which could be addressed in future studies. First, study has considered limited number of logistic indicators for analyzing their impact on the circular economy. Second, application of some advanced panel models like GMM is missing which may provide some different findings in future research. Third, only four ASEAN members are selected from the entire population. It is suggested that future studies can also conduct a cross-sectional or time series analysis on a similar topic too.